CHANGING CUSTOMER PREFERENCES IN THE FASHION INDUSTRY AND THEIR IMPACT ON SUPPLY CHAIN CONFIGURATION - N. Yu. Barkova (Вестник университета, 2020)
The issues related to changing customer preferences in the fashion industry have been considered. Changing consumer preferences, according to the author, can have an impact on the configuration of supply chains in the fashion industry. Among such new requirements of consumers in the fashion industry, the author have highlighted: consumer requests for the fastest possible receipt of products, production of products for specific individual requests of buyers, requests for transparency of supply chains and some others. In such situation, owners of clothing and footwear brands can cope with the new challenges of the company by re-shoring production with the organization of digital, robotic production factories.